Weed control with preemergence herbicides in sunflower - Durigan, Julio Cezar; Motta, Marcos (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this experiment was to test different preermergence herbicides, applied separately or in mixtures, during both dry and rainy sowing seasons, in sunflower (Helianthus annuus L.). The efficiency upon weed control and selectivity to the crop was evaluated. The experimental design used in both tests was in randomized blocks with ten treatments and four replications. Pendimethalin, alachlor, pronetryn, and linuron herbicides were tested isolately at rates of 1.25; 2.15; 1.60; and 1.00 kg/ha, or in mixtures at rates of 0.625; 1.075; 0.800; and 0.500 kg/ha, respectively. At the rainy season the weeds, mainly grasses, were more competitive and agressive than at the dry season, reaching differences up to 62.8% on the final yield of achenes. The best results of weed control (80% to 92%) were obtained with the herbicides alachlor and pendimethatin, and it was observed that, for the rainy season, these herbicides mixed with linuron or prometryn showed even better results (93% to 94%). None of the herbicides, isolated or in mixtures, showed any phytotoxicity with evident intoxication symptoms (visually observed) besides not damaging the stand and the achene yield.